Replication of Alphaviruses: A Review on the Entry Process of Alphaviruses into Cells - Jason Yat-Sing Leung; Mary Mah-Lee Ng; Justin Jang Hann Chu (Advances in Virology, 2011)
Alphaviruses are small, enveloped viruses, ~70 nm in diameter, containing a single-stranded, positive-sense, RNA genome. Viruses belonging to this genus are predominantly arthropod-borne viruses, known to cause disease in humans. Their potential threat to human health was most recently exemplified by the 2005 Chikungunya virus outbreak in La Reunion, highlighting the necessity to understand events in the life-cycle of these medically important human pathogens. The replication and propagation of viruses is dependent on entry into permissive cells. Viral entry is initiated by attachment of virions to cells, leading to internalization, and uncoating to release genetic material for replication and propagation. Studies on alphaviruses have revealed entry via a receptor-mediated, endocytic pathway. In this paper, the different stages of alphavirus entry are examined, with examples from Semliki Forest virus, Sindbis virus, Chikungunya virus, and Venezuelan equine encephalitis virus described.